Grapho-analytical method for determining possibilities of using discrete multiuse (DMu) resources in civil engineering companies - Tamošaitis, Romualdas (Journal of Civil Engineering and Management, 2002)
DMu resources in civil engineering companies include: small teams of builders, equipment pieces for performing jobs, cranes and other building machines. Limited quantities of the DMu resources often predetermine the terms of building operations and other important indices characterising the activities of civil engineering companies. This article deals with grapho-analytical method for specifying numbers of variants of distributions DMu resources and simulation of possible variants of distributions in accordance with the real job conditions. Simulation of the variants of DMu resources of building companies has few stages. During the first stage it is necessary to determine the basic parameters of the task (the degree of providing the work programme with DMu resources, the number of DMu resources application variants, etc.). During the second stage, simulation of the variants of DMu resources application should be performed. The third stage should include the calculation of the economical efficiency of variants. As an experience shows, the largest amount of computation time may be saved and the problem solved in a most reasonable way, when the task parameters are calculated accurately during the first stage and then, according to these parameters, the second stage of the task is optimised. Besides, sometimes the simulation problem cannot be solved because of the shortage of DMu resources or due to an immense number of DMu resources application variants. It may require choosing another method for task solving or changing entirely the job performance conditions.Frist Published Online: 30 Jul 2012